Experiences of individuals with arthritis who participate in quilting-related leisure activities. (2nd October 2019) - Proffitt, Rachel; Abraham, Meredith; Hughes, Christina
Abstract: Background/Aims: Individuals with arthritis experience physiological impacts from the condition that affect their participation in everyday activities. The latest literature suggests a need for more in-depth exploration of how hand impairments impact participation in leisure activities. This qualitative study explores the lived experience of individuals with arthritis who participate in quilting and sewing as a leisure activity. Methods: The Person-Environment-Occupation model provided a framework for this study. Semi-structured interviews were conducted with four individuals with arthritis. Participants interviewed in person also gave feedback on quilting tools. Results: Environmental supports (from tools or social circles) and physiological changes from the arthritis impacted performance of and participation in quilting. The participants were already independently making modifications to maximise participation in quilting and sewing, even though none had consulted with health care professionals. Conclusions: Knowledge of task analysis and ergonomics allows occupational therapists to support performance through collaboration with clients on modifications to support participation.